2017
DOI: 10.4172/2161-0711.1000551
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities and Barriers to the Use of Health Care among Cancer Patients in the Pacific: A Systematic Review

Abstract: Introduction and aim: According to the WHO, the cancer threat is expected to rise by over 70% within the next two decades. To prevent cancer and reduce the consequences of cancer among patients it is essential to understand the barriers. Due to the close relation between the barriers, and also inequality on one side and lack of previous study among Pacific countries on the other side, this systematic review was conducted to understand inequalities and barriers to the use of health care among cancer patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
3
2
0
Order By: Relevance
“…Due to lack of financial resources most women cannot travel to seek health services for screening and later on for treatment. These findings are in tandem with those of Mohammadnezhad et al [17] and Kuguyo et al [5] who reported limited and centralized screening and treatment services in low-income contexts.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Due to lack of financial resources most women cannot travel to seek health services for screening and later on for treatment. These findings are in tandem with those of Mohammadnezhad et al [17] and Kuguyo et al [5] who reported limited and centralized screening and treatment services in low-income contexts.…”
Section: Discussionsupporting
confidence: 86%
“…Bad attitude towards patients with chronic diseases by health workers play a significant role in undermining health seeking behaviors [19] and may lead to patients resorting to alternative interventions. Unavailability of adequately trained health workforce reduces the availability of diagnosis and treatment services [17, 20]. Studies in the USA have reported that deficiency of knowledge and lack of training of health workers were barriers to cancer services supporting our findings [20, 21].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…A qualitative exploratory descriptive and contextual research design was utilised to explore and describe the barriers to accessing oncology services for effective cancer care in the public health institutions in Limpopo province [11]. The qualitative exploratory design research approach assists researchers in understanding the natural context of the participants as they detail how they experience the phenomena under study; the researchers can capture meaningful characteristics related to real-life events as experienced and narrated.…”
Section: Methodsmentioning
confidence: 99%